Anything but plain [large type] - Fisher, Suzanne Woods (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"Lydie Stoltzfus has always felt like a square peg in a round hole in her quiet Amish community. Even though she's the bishop's daughter, it seems the only thing she does well is disappoint others. Leaving Stoney Ridge seems like her best move-- even though it would mean leaving Nathan Yoder behind. Nathan claims he's in love with her, but Nathan's father reminds her frequently that she is not good enough for him. When the local doctor asks Lydie to fill in at the front desk for a few months, the Dok makes a discovery that could change Lydie's life."-- adapted from back cover